Differences in pedalling technique between road cyclists of different competitive levels - Garcia-Lopez, J.; Diez-Leal, S.; Ogueta-Alday, A.; Larrazabal, J.; Rodriguez-Marroyo, J. A. (Journal of Sports Sciences, 2016)
The purpose of this study was to compare the pedalling technique in road cyclists of different competitive levels. Eleven professional, thirteen elite and fourteen club cyclists were assessed at the beginning of their competition season. Cyclists` anthropometric characteristics and bike measurements were recorded. Three sets of pedalling (200, 250 and 300 W) on a cycle ergometer that simulated their habitual cycling posture were performed at a constant cadence (~90 rpm), while kinetic and kinematic variables were registered. The results showed no differences on the main anthropometric variables and bike measurements. Professional cyclists obtained higher positive impulse proportion (1.5-3.3% and P < 0.05), mainly due to a lower resistive torque during the upstroke (15.4-28.7% and P < 0.05). They also showed a higher ankle range of movement (ROM, 1.1-4.0° and P < 0.05). Significant correlations (P < 0.05) were found between the cyclists` body mass and the kinetic variables of pedalling: positive impulse proportion (r = -0.59 to -0.61), minimum (r = -0.59 to -0.63) and maximum torques (r = 0.35-0.47). In conclusion, professional cyclists had better pedalling technique than elite and club cyclists, because they opted for enhancing pulling force at the recovery phase to sustain the same power output. This technique depended on cycling experience and level of expertise.